Information-Seeking Behavior among Non-Traditional Learners in Online Education Platforms - Mathan, N.; Wunnava, Aneesh; Pandey, Sumukh; Tejeshwari, M. R.; Verma, Lokesh (Indian Journal of Information Sources and Services, 2025)
Aim: As online education continues to evolve, it increasingly attracts non-traditional learner’s individuals who diverge from the conventional college-aged, full-time student demographic- including adult learners, part-time students, career-switchers, and lifelong learners. Understanding how these learners seek, evaluate, and utilize information within online learning platforms is essential for enhancing educational design and learner engagement. It investigates the information-seeking behavior of non-traditional learners across various online education platforms, learning management systems, and informal learning resources. Methodology: A mixed-methods approach was adopted, combining survey data (n = 486), semi-structured interviews (n = 30), and platform usage analytics. Quantitative data were analyzed using descriptive statistics, chi-square tests, and logistic regression models to identify significant predictors of effective information-seeking behavior by utilizing SPSS version 28. Result: That reveals that 68.5% of participants relied primarily on external resources alongside platform content. Chi-square analysis showed a significant association between age group and preference for multimedia resources (χ² = 24.73, p < 0.001), and logistic regression identified digital literacy level (OR = 2.14, CI = 1.58–2.89, p < 0.001) as a strong predictor of proactive information-seeking strategies. Moreover, time constraints (reported by 74.2%) and difficulty navigating course interfaces (62.8%) emerged as key obstacles. Conclusion: The research concludes with recommendations for integrating adaptive learning features, personalized search support, and modular content presentation to enhance user experience. This research contributes to the growing discourse on learner diversity in online education and offers actionable insights for pedagogy, policy, and platform development.